PENGARUH MANAJEMEN SUMBER DAYA MANUSIA, STANDAR OPERASIONAL PROSEDUR DAN TEKNOLOGI INFORMASI TERHADAP KUALITAS PELAYANAN TERPADU SATU PINTU (PTSP) KANTOR KEMENTERIAN AGAMA KABUPATEN TAPIN - Yudi Rahman; Risna Afriyanti; Fauziannor; Fakhri (Jurnal Ilmiah Ekonomi Bisnis, 2024)
ABSTRACT The purpose of this study was to determine and analyze the significant influence simultaneously, partially and dominantly on Human Resource Management, Standard Operating Procedures and Information Technology on the Quality of One Stop Service (PTSP) of the Office of the Ministry of Religion in Tapin Regency. Data analysis techniques were carried out by collecting and analyzing data obtained from field research using a method that is simple quantitative description. The population in this study were all employees of the Ministry of Religion of Tapin Regency, both civil and honorary civil servants, totaling 62 people. Considering that the population in this study was less than 100 people, the sampling in this study used saturated sampling, namely a technique in which all populations were used as samples, namely as many as 62 people. Data collection techniques were by observation, documentation, questionnaires, and interviews. Validity and reliability tests were carried out on research instruments. Data were analyzed by means of: Normality Test, Multicollinearity Test, Heteroscedasticity Test, Linearity Test. The results of the study show that Human Resource Management and Standard Operating Procedures have a significant simultaneous and partial effect on the One Stop Service Quality (PTSP) of the Ministry of Religion in Tapin district. And Information Technology has no significant effect partially on the Quality of One-Stop Integrated Service (PTSP) of the Ministry of Religion in Tapin district. It is recommended for all employees of the Tapin district Ministry of Religion Office to improve the implementation of Standard Operating Procedures.